Acute rheumatic fever mimicking an acute coronary syndrome. Issue 8 (20th July 2006) - Turley, A J; McCarron, B; de Belder, M A
Abstract : An elevated troponin measurement does not always reflect myocardial ischaemia secondary to obstructive coronary artery disease. Troponin levels can also be elevated in other disease states including pulmonary emboli, myo-pericarditis, acute rheumatic fever, and in the critically ill. Thus, patients presenting with chest pain and electrocardiological and biochemical evidence of myocardial necrosis are not always suffering from an acute coronary syndrome.